D-Dimer In Pregnancy - Danny Ernest Jonas Luhulima; Batara Imanuel Sirait (International Journal of Health Engineering and Technology, 2026)
D-dimer is a fibrin degradation product that serves as a vital biomarker in the fibrinolytic system. This review aims to examine the role and mechanism of D-dimer during pregnancy and its measurement methods. The method used is a literature review of clinical studies and references related to hemostasis in pregnancy. Results show that pregnancy physiologically increases coagulation activity as a natural mechanism to prevent hemorrhage during delivery. Increased D-dimer levels are found in 27% of first-trimester pregnancies, 87% in the second trimester, and 100% in the third trimester. Pathological conditions such as preeclampsia, eclampsia, and venous thromboembolism (VTE) risks are closely linked to significant surges in D-dimer levels. While ELISA remains the gold standard for D-dimer testing, immunoturbidimetric and immunofiltration methods are more commonly used due to their speed and efficiency. In conclusion, although D-dimer levels naturally rise during pregnancy, monitoring this parameter is crucial for predicting medical emergencies like disseminated intravascular coagulation (DIC) to reduce maternal mortality rates.